Analysis of environmental regulation policy for Chinese paper enterprises - Zhengxia He; Wenqi Lu; Xin Guo; Wenxing Shen; Xu Wang; Cunfang Li; Wenbo Li (BioResources, 2020)
In the past decade, the Chinese paper industry, which is highly polluting and energy intensive, has shown overall increases in production, sales, income, and profit, although the growth rate has declined. Overall, China’s paper industry exhibits small-scale and scattered distribution, characterized by continuous overcapacity and outdated technical knowledge. This has inevitably resulted in a variety of serious environmental problems during its development. Owing to the environmental problems resulting from the development of the paper industry, various environmental regulatory policies and measures have been adopted in China, mainly command-and-control, market-based, and voluntary policies and measures. This study identifies and analyzes particular issues inherent to China’s environmental regulatory policies and measures regarding the paper industry and proposed policy suggestions for improving the environmental regulation of China’s paper industry.